Current State Of The Process Of Designing Clothes For Children With Cerebral Palsy And Ways Of Improvement - Abdushukurova, Yulduz (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
One of the goals of rehabilitation of children with disabilities is to improve their quality of life. The work examines the interaction of the systems "society" - "textile rehabilitation means" - "child". It is determined that textile rehabilitation means, including inclusive clothing, affect not only the condition of the child, but also the emotional state of the society in contact with him, especially his parents. The article describes the main principles of designing textile rehabilitation means and inclusive clothing for children with disabilities, which are aimed at harmonizing the perception of the child’s appearance.